Magnetic and structural studies of vanadium arene complexes - Beck, V; Cowley, A; O'Hare, D (2004)
The temperature dependence of the solid-state magnetic susceptibility for the paramagnetic V(I) complexes trans-(CpV)2(μ-n 6:n6-C6H6) (1) and CpV(n 6-C6H6) (2) has been investigated. Complex 1 obeys the Curie-Weiss law over the temperature range 10-300 K with μ eff = 4.81 μB and Θ = -18.8 K. The high-temperature moment is consistent with the presence of a total of four unpaired electrons derived from two low-spin V(I) d4 metal centers in an S = 2 configuration. However, at ca. 9 K the magnetic susceptibility displays a broad maximum. This magnetic behavior may be modeled over the full temperature range (4-300 K) using the Heisenberg intracluster magnetic exchange expression for an S1 = S2 = 1 system with g = 2.37, Θ = -12.3 K, and J = -2.64 cm-1. Complex 2 obeys the Curie-Weiss law over the temperature range 5-300 K, with μeff = 2.86 μB and Θ = -5.0 K. The X-ray structure of 2 (P2 1/a, a = 10.7842(4) Å, b = 7.8233(4) Å, c = 11.2017(5) Å, β= 113.830(2)° at 150 K, Z = 4) has been determined. Crystals of 2 undergo a reversible phase transition to a new monoclinic cell with a' ≈ (a + c)/2, b' ≈' b, c' ≈ (c -a)/2 over the temperature range 290-270 K.